?NUTRITIONAL CHANGES IN MILK DURING HEAT TREATMEN (CHANGES IN CARBOHYDRATES AND LYSINE CAUSED BY HEATING MILK) (Biological Sciences - PJSIR, 1994)
Degradation of lactose and lysin in milk during heating at various temparatures (90-150·) for different intervals of time was investigated. Reduction in lactose and available lysine contents alongwith the formation of lactulose, galac- tose and hydroxymethyl furfural (HMF) was observed due to heat treatment. The concentration oflactose and lysine was reduced from 4.81-3.52% and 21-.0-18.63 m. mole respectively when milk was heated at 150· for 10 mins, Maximum concentration of lactulose, glactose and HMF in 150·-10 mins. heated milk were 791.5, 178.1 mg% and 166.21 ~ M. The energy of activation of the reduction in lactose and available lysine contents was 102.32 and 50.87 Kl/mole respectively. However, the energy of activtion was 101.57 Kl/mole for the formation of lactulose, 60.68 Kl/mole for galactose and 122.21 Kl/mole for HMF in heated milk.